Bioremediation at a global scale: from the test tube to planet Earth. Issue 5 (4th August 2016) - de Lorenzo, Víctor; Marlière, Philippe; Solé, Ricard
Summary: Planet Earth's biosphere has evolved over billions of years as a balanced bio‐geological system ultimately sustained by sunpower and the large‐scale cycling of elements largely run by the global environmental microbiome. Humans have been part of this picture for much of their existence. But the industrial revolution started in the XIX century and the subsequent advances in medicine, chemistry, agriculture and communications have impacted such balances to an unprecedented degree – and the problem has nothing but exacerbated in the last 20 years. Human overpopulation, industrial growth along with unsustainable use of natural resources have driven many sites and perhaps the planetary ecosystem as a whole, beyond recovery by spontaneous natural means, even if the immediate causes could be stopped. The most conspicuous indications of such a state of affairs include the massive change in land use, the accelerated increase in the levels of greenhouse gases, the frequent natural disasters associated to climate change and the growing non‐recyclable waste (e.g. plastics and recalcitrant chemicals) that we release to the Environment. While the whole planet is afflicted at a global scale by chemical pollution and anthropogenic emissions, the ongoing development of systems and synthetic biology, metagenomics, modern chemistry and some key concepts from ecological theory allow us to tackle this phenomenal challenge and propose large‐scale interventions aimed at reversing and even improving the situation. This involves (i) identification of key reactions or processes that need to be re‐established (or altogether created) for ecosystem reinstallation, (ii) implementation of such reactions in natural or designer hosts able to self‐replicate and deliver the corresponding activities when/where needed in a fashion guided by sound ecological modelling, (iii) dispersal of niche‐creating agents at a global scale and (iv) containment, monitoring and risk assessment of the whole process. Abstract : Recent developments of systems and synthetic biology as well as new ecology theory enable considering the whole planet as the target for global bioremediation interventions aimed at restoring the balances hit otherwise by human (industrial, urban, agricultural) activity. The benefits versus risks of such technologies need to be weighted and the resulting evidence used for guiding their deployment.